Patient weight has diverse effects on the prescribing of different antibiotics to dogs - Becker, Stuart D.; Hughes, David M. (Frontiers in Veterinary Science, 2024)
Various factors including body weight-associated treatment cost may influence the probability of dispensing antibiotics to dogs in first-opinion practice, but their effect on specific drug choice remains unclear.Methods: Multiple membership regression modelling was used to investigate the probability of dispensing twelve different antibiotics to dogs of different weights in the context of various disease presentations, using anonymised data obtained from electronic health records of 18 clinics between 2020 -2022. Data from 14,259 dogs were analysed.Results: Treatment choice varied significantly with animal weight. Higher body weight was associated with an increased likelihood of dispensing lower cost antimicrobials such as amoxicillin and trimethoprim sulfonamide, while use of higher cost antimicrobials such as cefovecin was strongly biased to smaller animals. However, these effects were limited when restricted treatment options were available for the target condition.This work demonstrates that anticipated financial costs may result in different treatment choices for canine patients depending on their body weight. Further work is needed to understand the impact of financial pressures on veterinarians' treatment choices, and the implications for the optimisation of antimicrobial stewardship in first opinion practice.